The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.7150/ijms.6054
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Implications of the Expression of Hypoxia-related Proteins in Gastric Cancer

Abstract: Objectives: Tumor hypoxia confers poor prognosis of a wide range of solid tumors due to increased malignancy, increased likelihood of metastasis and treatment resistance. The aim of this study was to assess the significance of the expression of HIF-1α and HIF-1α-inducible proteins in gastric cancer and their impact on prognosis. Materials and Methods: The expression of HIF-1α, GLUT-1, CA-9, and iNOS proteins was analyzed by immunohistochemistry in 193 gastric adenocarcinomas (GAs) and 20 normal gastric mucosa.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 23 publications
3
30
1
Order By: Relevance
“…Previous reports showed sCA9, SCF, and MIP-1a are associated with a hypoxic signature [18,[28][29][30]. As intestinal-type GC is partially caused by Helicobacter pylori-associated metaplasia and mediated by hypoxia-induced angiogenesis [31,32], as such, increased levels of sCA9 in intestinal-type disease compared to the diffuse-type disease would be reasonable. Moreover, as signet ring cell pathology is associated with diffuse-type disease [21,33], it is expected that serum levels of SCF and MIP-1a would be lower in patients with signet ring cell components.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports showed sCA9, SCF, and MIP-1a are associated with a hypoxic signature [18,[28][29][30]. As intestinal-type GC is partially caused by Helicobacter pylori-associated metaplasia and mediated by hypoxia-induced angiogenesis [31,32], as such, increased levels of sCA9 in intestinal-type disease compared to the diffuse-type disease would be reasonable. Moreover, as signet ring cell pathology is associated with diffuse-type disease [21,33], it is expected that serum levels of SCF and MIP-1a would be lower in patients with signet ring cell components.…”
Section: Discussionmentioning
confidence: 99%
“…9 GLUT-1 expression is associated with poor prognosis in several tumors such as cervical squamous cell carcinoma, 10 epithelial ovarian cancer, 11 and gastric carcinoma. 12 In Egypt, skin cancer is common among elderly males; its etiology is related to sun exposure and it represents 5% of the malignant tumors of the entire body. Basal cell carcinoma (BCC; 77%) was the most common skin cancer followed by squamous cell carcinomas (SCCs; 15%) and melanomas (8%).…”
Section: Introductionmentioning
confidence: 99%
“…Its expression in gastric cancer is associated with increased invasion, supporting the hypothesis that increased CAIX expression may contribute to invasion and thus advanced disease and tumor progression 34 . The presence of CAIX has also been linked with poorer survival/prognosis in several other solid tumors 15,16,26,30,31 . In neuroblastoma, a previous study has shown that CAIX is expressed at significantly higher levels in tumors from patients with adverse clinicopathological and biological factors 18 .…”
Section: Impact Of Caix Expression and Survivalmentioning
confidence: 99%
“…HIF-1alpha, CAIX and GT-1 (glucose transporter-1) are well-established prognostic markers in solid cancers 26 . The hypoxia-dependent expression of CAIX has been described for many solid tumors, including gastric cancer 26,27 , breast cancer 28 , prostate cancer 14 , colon cancer 29 , oral squamous cell cancer 16 , esophageal cancer 30,31 , where it is associated with malignant phenotype 31 , adverse clinicopathological factors 18 , tumor cell dissemination 29,32,33 and poor survival 15,16,26,30,31 . Carbonic anhydrase IX has been shown to be involved in numerous pathological processes including tumorgenicity 16 and was suggested to be involved in malignant transformation 34 .…”
Section: Impact Of Caix Expression and Survivalmentioning
confidence: 99%
See 1 more Smart Citation